2022
DOI: 10.37231/ajmb.2022.6.s1.572
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative and Apoptosis Inducing Effects of Gallic Acid on Human Acute Myeloid Leukaemia Cell Lines (HL-60)

Abstract: Gallic acid (GA) comes from benzoic acid or, more specifically, 3,4,5-tryhydroxybenzoic, which derives from the phenolic acid of the non-flavonoid part of the polyphenol compound. It is found ubiquitously in various plants and fruits, such as grapes, gallnuts, pomegranates, and tea leaves [1]. Many scientific journals and articles reported on the pharmacological properties of the photochemical like GA, which has antioxidant properties, antimicrobial, anti-inflammatory, anticancer, cardioprotective, gastroprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Owing to its anticancer, antioxidant, antimicrobial, and anti-inflammatory capabilities, gallic acid has therapeutic applications in treating multiple medical conditions including GI infections, neurological diseases, and heart disorders ( Kahkeshani et al., 2019 ; Shukla et al., 2022 ). Gallic acid was reported to induce apoptosis in leukemia HL60 cell lines owing to its antitumor and anti-proliferative effects observed in multiple studies ( Maruszewska and Tarasiuk, 2019 ; Soto-Maldonado et al., 2019 ; Roba’ei et al., 2022 ). Gallic acid also showed potent anti-obesity properties by directly targeting adipose tissue and inhibiting lipogenesis ( Dludla et al., 2018 ), which was reported upon administration of ethyl acetate extract of A. xanthioides to high-fat-diet mouse and rat models ( Kim et al., 2015 ; Im et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its anticancer, antioxidant, antimicrobial, and anti-inflammatory capabilities, gallic acid has therapeutic applications in treating multiple medical conditions including GI infections, neurological diseases, and heart disorders ( Kahkeshani et al., 2019 ; Shukla et al., 2022 ). Gallic acid was reported to induce apoptosis in leukemia HL60 cell lines owing to its antitumor and anti-proliferative effects observed in multiple studies ( Maruszewska and Tarasiuk, 2019 ; Soto-Maldonado et al., 2019 ; Roba’ei et al., 2022 ). Gallic acid also showed potent anti-obesity properties by directly targeting adipose tissue and inhibiting lipogenesis ( Dludla et al., 2018 ), which was reported upon administration of ethyl acetate extract of A. xanthioides to high-fat-diet mouse and rat models ( Kim et al., 2015 ; Im et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its anticancer, antioxidant, antimicrobial, and antiinflammatory capabilities, gallic acid has therapeutic applications in treating multiple medical conditions including GI infections, neurological diseases, and heart disorders (Kahkeshani et al, 2019;Shukla et al, 2022). Gallic acid was reported to induce apoptosis in leukemia HL60 cell lines owing to its antitumor and anti-proliferative effects observed in multiple studies (Maruszewska and Tarasiuk, 2019;Soto-Maldonado et al, 2019;Roba'ei et al, 2022). Gallic acid also showed potent anti-obesity properties by directly targeting adipose tissue and inhibiting lipogenesis (Dludla et al, 2018), which was reported upon administration of ethyl acetate extract of A. xanthioides to high-fat-diet mouse and rat models (Kim et al, 2015;Im et al, 2020).…”
Section: Total Phenolics and Flavonoidsmentioning
confidence: 99%